Sending-Terminal DC Power Grid in Western China and Its Operation Characteristics in the Context of New Power System - Huiling LI (Zhongguo dianli)
Inevitably China will encounter the enormous demand of large-capacity power transmission over long-distance transmission from the west to the east in the future. With regards to such emerging requirement, a cluster-connected western sending terminal DC grid based on VSC-HVDC is constructed in this paper such that the complementary regulation is performed between different power sources such as wind power, solar power, hydro power and thermal power in Western China, and the problem of randomness and fluctuation of renewable energy can also be addressed. The simulation system of the western sending terminal DC grid is set up based on the studies of the steady-state model, transient model and coordinated control strategy. Furthermore, the steady-state operation characteristics and transient operation characteristics of the western sending terminal DC grid are analyzed, as well as the impact of large renewable energy generation fluctuation on the operation of DC grid. The results show that, in view of the power change of the renewable energy converter stations caused by AC/DC fault and power fluctuation due to the weather reasons, power generation can be coordinated among the converter stations to achieve emergency backup of all kinds of energy sources and reduce the disturbance impact. Therefore, the western sending terminal DC grid can realize the stable long-distance transmission of large-scale renewable energy.